The Impact of The Application of Forensic Accounting on Fraud: A Literature Study - Padri Achyarsyah; Muhammad Nur; Erwin Indriyanto; Kumba Digdowiseiso; Safwan Mohd Nor (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This research discusses the importance of forensic accounting in overcoming fraud in modern business. This research uses a literature study and the research methodology involves identifying relevant literature sources from academic databases, journals, books and related articles. The research focus is on forensic accounting concepts, investigative techniques, and audit methods used to identify fraud. The research results show that forensic accounting is an important method for uncovering, preventing and resolving fraud in the accounting field. The application of forensic accounting involves technology and computer-assisted investigative methods to identify fraud. Case studies show that careful analysis and firm legal action can address fraud, reduce the risk of fraud, and increase stakeholder trust. Forensic accounting also has a positive impact on financial reports and a company's reputation by increasing the transparency, accuracy and integrity of financial reports. However, the implementation of forensic accounting faces obstacles such as regulatory complexity, costs, and the need for trained human resources. To overcome these obstacles, companies can develop specialized training, collaborate with educational institutions, and invest in the right technology. By overcoming these obstacles, companies can ensure the reliability of financial reports, improve their reputation, and maintain the integrity of their operations in the face of increasingly complex and organized fraud threats. Thus, forensic accounting has proven to be effective as an important tool in overcoming fraud and maintaining company business sustainability